Physical and microbiological quality and oxidative stability in different storage periods of Angus-Nellore heifer meat in an integrated livestock-forest system - da Luz Zanetti, Patrícia Aparecida; Mateus, Gustavo Pavan; Lupatini, Gelci Carlos [UNESP]; Zanetti, Leonardo Henrique; Vieira, Natália Carolina; de Oliveira Neves, Franciely [UNESP]; de Freitas Santos, Juliana Mara [UNESP]; Trivelin, Gustavo Antunes [UNESP]; Mazetti, Estevão Moretti [UNESP]; Andrighetto, Cristiana [UNESP] (Universidade Estadual de Londrina, 2024)
This study aimed to evaluate the physical and microbiological quality as well as the oxidative stability of meat stored frozen (30, 60, 90, 180, and 360 days) and obtained from Angus-Nelore heifers kept in a conventional system (CS; no shade available) and Integrated Livestock-Forest (ILF-1L and ILF-3L). Forty-eight ½ Nellore ½ Angus heifers with an average initial weight of approximately 276.70 ± 20.1 kg and an average age of nine months were distributed across a randomized block design with three treatments and four replicates. After slaughter, the Longissimus thoracis muscle was collected from each carcass for pH, lipid oxidation, meat color, and microbiological analyses. The physical and microbiological quality and oxidative stability of the meat were not affected by the tree component present in the pasture. Regarding the duration of frozen storage, it was found that the pH, meat color (a*, b*, C*, H*, O/M), and lipid oxidation increased as the period of storage increased (P<0.05). The physical and microbiological quality, as well as the oxidative stability of the meat, was not affected by the tree component present in the pasture. However, the meat changed as the frozen storage time increased.
Qualidade física e microbiológica e estabilidade oxidativa em diferentes períodos de armazenamento da carne de novilhas Angus-Nelore em integração pecuária-floresta
Keywords: Industrial crossing; Longissimus thoracis; pH; Silvopastoral system; Total bacteria count